Peran Kepemimpinan Gen-Z: Mengembangkan Kemampuan dan Keterampilan Kepemimpinan Remaja dalam Kekristenan : Mengembangkan kemampuan dan ketrampilankepemimpinan Remaja dalam Kekristenan - Imel Yovita; C Angelina (Sekolah Tinggi Teologi Satyabhakti, East Java, 2025)
Efficient leadership can help teenagers develop responsibility, leadership skills, and social maturity, which are crucial for developing leadership abilities. Efficient leadership is not just about taking control; it involves leading with empathy, listening, and inspiring team members. Leadership skills are crucial for a leader to possess, as they can encourage growth and development within their immediate environment, both now and in the future. A leader must also be a good example for others. He or she must be able to demonstrate a positive attitude that is worthy of emulation. Leadership should be cultivated from adolescence, as this age is ideal for the formation of individual character rooted in Christian values. Good leadership does not necessarily mean being able to lead others, but rather being able to lead oneself well. Therefore, cultivating leadership skills from adolescence can help individuals become better leaders in the future, with strong character rooted in Christian values.